Comparative Genomic Analysis of Tigecycline Resistance Development in Clinical Acinetobacter baumannii Isolates - Li X; Liu J; Zhang X; Li J; Xuan L; Yuan S; Li J; Sun Y; Du X (Infection and Drug Resistance)
Xiaoxia Li,1,* Junnian Liu,2,* Xinyu Zhang,1 Juan Li,3 Luhan Xuan,1 Sue Yuan,1 Jianglin Li,1 Yu Sun,1 Xuefei Du1 1Clinical Laboratory, the Fourth Affiliated Hospital of Harbin Medical University, Harbin, Heilongjiang, People’s Republic of China; 2Department of Blood Transfusion, the First Affiliated Hospital of Harbin Medical University, Harbin, Heilongjiang, People’s Republic of China; 3Department of Clinical Laboratory, Yunnan Fuwai Cardiovascular Disease Hospital, Kunming, Yunnan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xuefei Du, Clinical Laboratory, the Fourth Affiliated Hospital of Harbin Medical University, Harbin, No. 37, Yiyuan Jie, Nangang District, Harbin, Heilongjiang, 150001, People’s Republic of China, Email duxuefei82@163.com Yu Sun, Email 249292018@qq.comObjective: This study investigated the mechanisms underlying the reduced tigecycline sensitivity of Acinetobacter baumannii strains isolated from infected patients during antimicrobial therapy. The goal is to provide clinical insights into the development of tigecycline resistance in A. baumannii, with a focus on multidrug-resistant strains commonly associated with hospital-acquired infections.Methods: We conducted dynamic tracking of multidrug-resistant Acinetobacter baumannii (MDR-AB) infections in three patients to monitor changes in tigecycline sensitivity during antimicrobial therapy. From each patient, tigecycline-sensitive and -resistant A. baumannii strains were collected and paired into groups. A total of six strains were subjected to molecular typing and phylogenetic analysis to assess the genetic homology between the tigecycline-sensitive and -resistant strains within each group. Whole-genome sequencing and comparative genomic analysis were performed to identify single nucleotide polymorphisms and small insertions/deletions between paired strains, aiming to pinpoint mutated genes. Gene knockout experiments were conducted to validate the role of the identified genes in modulating tigecycline sensitivity and contributing to the development of tigecycline resistance in A. baumannii.Results: Molecular typing and phylogenetic analysis confirmed that the tigecycline-resistant Acinetobacter baumannii strains isolated from each patient evolved from the initially infecting tigecycline-sensitive strains. All three patients had received tigecycline therapy before the emergence of tigecycline resistance. Notably, in one patient, resistance developed 21 days after discontinuing tigecycline treatment. Comparative genomic analysis of the paired strains revealed point mutations in the conserved domain of the trimeric autotransporter adhesin in all three groups. Additionally, a frameshift mutation in the acrR gene was identified in two of the three groups. To investigate the role of acrR in the development of tigecycline resistance, an acrR knockout strain was constructed. The results indicated that the acrR gene did not significantly impact tigecycline resistance or biofilm formation.Conclusion: The use of tigecycline promotes the development of tigecycline resistance in Acinetobacter baumannii, and resistance may continue to evolve even after discontinuing tigecycline treatment. Mutations in the ata, adeS, and acrR genes may contribute to the development of tigecycline resistance in A. baumannii. Although gene knockout experiments in this study showed that acrR did not directly impact tigecycline resistance or biofilm formation, clinical isolates are influenced by a complex, multifactorial environment. Therefore, the role of acrR warrants further investigation.Keywords: Acinetobacter baumannii, tigecycline, comparative genomics